Optical in-situ measurements and modeling of post-flame sulfation of NaOH(g) and NaCl(g) - Schmid Daniel; Weng Wubin; Li Shen; Karlström Oskar; Hupa Mikko; Li Zhongshan; Glarborg Peter; Marshall Paul; Aldén Marcus (Elsevier Ltd, 2025)
Post-flame sulfation of gaseous sodium hydroxide (NaOH) and sodium chloride (NaCl) was investigated with optical in situ measurements at 850 to 1475 ◦C. A multi-jet burner was used to generate well-controlled combustion environments. The multi-jet burner also enabled the separate feeding of the sodium species and SO2 to the combustion environment where the sulfation reactions occurred. Concentrations of NaOH(g) and NaCl(g) were measured in the product gas using broadband UV absorption spectroscopy to follow the degree of sulfation. At 1475 and 1275 ◦C almost no sulfation occurred with an initial NaOH(g) concentration of 20 ppm and SO2 concentrations between 0 and 150 ppm. At 985 ◦C, the NaOH(g) concentration decreased to less than 5 ppm with SO2 concentrations above 50 ppm and at 850 ◦C almost all NaOH(g) was sulfated under these conditions. The experimental results for the gas-phase sulfation of NaOH were compared to previous results for the sulfation of KOH under the same conditions and the results were shown to be similar for NaOH and KOH under these conditions. Sulfation of NaOH(g) generally occurred to a more significant extent than the sulfation of NaCl(g). At 1115 to 1475 ◦C, no sulfation of NaCl(g) was observed. At the lowest investigated temperature, 850 ◦C, the NaCl (g) concentration decreased from 20 ppm to 12 ppm after the addition of 150 ppm SO2. Chemical equilibrium calculations and kinetic modeling using an updated kinetic model for the detailed Na-Cl-S chemistry were compared to the experimental results. Above 1100 ◦C, the system can be described by chemical equilibrium, implying that equilibrium is reached in less than 100 ms. At temperatures below 1100 ◦C, the measured concentration indicated kinetic control. Under these conditions, the kinetic model was in good agreement with the experimental results for NaOH(g) but over-predicted the sulfation of NaCl(g). The combined experimental data, chemical equilibrium calculations and kinetic modeling of the present study support that sulfation of alkali species can occur in the gas phase through homogeneous reactions.